AN EVALUATION OF PROGRAMMED TREATMENT‐INTEGRITY ERRORS DURING DISCRETE‐TRIAL INSTRUCTION. Issue 2 (23rd May 2013) - Carroll, Regina A.; Kodak, Tiffany; Fisher, Wayne W.
Abstract This study evaluated the effects of programmed treatment‐integrity errors on skill acquisition for children with an autism spectrum disorder (ASD) during discrete‐trial instruction (DTI). In Study 1, we identified common treatment‐integrity errors that occur during academic instruction in schools. In Study 2, we simultaneously manipulated 3 integrity errors during DTI. In Study 3, we evaluated the effects of each of the 3 integrity errors separately on skill acquisition during DTI. Results showed that participants either demonstrated slower skill acquisition or did not acquire the target skills when instruction included treatment‐integrity errors.